2017
DOI: 10.1377/hlthaff.2017.0774
|View full text |Cite
|
Sign up to set email alerts
|

Rising Use Of Observation Care Among The Commercially Insured May Lead to Total And Out-Of-Pocket Cost Savings

Abstract: Proponents of hospital-based observation care argue that it has the potential to reduce health care spending and lengths-of-stay, compared to short-stay inpatient hospitalizations. However, critics have raised concerns about the out-of-pocket spending associated with observation care. Recent reports of high out-of-pocket spending among Medicare beneficiaries have received considerable media attention and have prompted direct policy changes. Despite the potential for changed policies to indirectly affect non-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…It is important to note, however, that for commercially insured patients, observation units reduce total out-of-pocket expenses. 23 Increasing the use of observation services may require further expanding the number of EDOUs in the US and evaluating payment options for Medicare beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that for commercially insured patients, observation units reduce total out-of-pocket expenses. 23 Increasing the use of observation services may require further expanding the number of EDOUs in the US and evaluating payment options for Medicare beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…The financial responsibilities for patients differ under the OPPS compared with the IPPS, with a shifting of payments from Medicare Part A (with a fixed inpatient deductible of $1,316 in 2017) to Part B (20% coinsurance for each service). While hospital-based outpatient surgery has a cap on the copayment that is similar to the inpatient deductible, there is no cap on ASC charges, so the 20% coinsurance rate can be charged for each service rendered, resulting in the possibility of paying multiple deductibles for different services related to a single TJA procedure 115,116 . One study of minor hand procedures found a lower average cost in the ASC relative to outpatient hospital setting ($709 versus $1,216) but a small increase in out-of-pocket expense for patients ($140 versus $116) for 1 private insurance provider 117 .…”
Section: Financial Implicationsmentioning
confidence: 99%
“…Similarly, for some patients with commercial insurance, the total and out-of-pocket spending has the potential to be much lower with observation care compared to hospital admission. [8] Regardless of the pros and cons of observation services for each individual patient, hospitals must adhere to Medicare rules, not patient requests. [9] An important role that UM departments play is ensuring regulatory compliance with state and federal laws and compliance with insurance contracts.…”
Section: Hidden Realities and The Imperative Of Regulatory Compliancementioning
confidence: 99%